From Metals to Composite Materials: A Comprehensive Review of ‎Materials Used in Prosthetic Limb Manufacturing (Journal of University of Babylon for Engineering Sciences, 2025)
The field of prosthetics has witnessed significant and extensive development with the advancement in the use of materials for prosthetic limbs. In the past, prosthetic limbs were made of wood, but the industry evolved to include metals and their alloys. However, the limitations of these materials, prompted researchers in the field of materials science to seek more advanced and flexible alternatives. Recently, there has been a shift towards using polymeric, composite materials, and fibers such as carbon and glass fibers due to their desirable properties, such as lightweight, strength for fibers, ease of shaping, and flexibility regards to polymers, which have made life easier for prosthetic users. This review showcases the developments in the manufacturing of prosthetic limbs in terms of the materials used and their suitability for each part of the lower limb prosthesis.